Population genomics reveals an ancient origin of heartworms in canids - Power, Rosemonde I.; Abdullah, Swaid; Walden, Heather S.; Verocai, Guilherme G.; Sanders, Tiana L.; Luksovsky, Joe L.; Moorhead, Andrew R.; Dzimianski, Michael T.; Foster, Jeremy M.; Michalski, Michelle L.; Rojas, Alicia; Chacón, Samuel C.; et al. (Nature Research, 2026)
Heartworms (Dirofilaria immitis) are parasitic nematodes that cause significant cardiopulmonary-associated morbidity and mortality in canids worldwide. The global spread of heartworms is believed to have occurred alongside the dispersal of modern domesticated dogs over the past few hundred years. However, this conclusion has been based on limited sampling, both geographically and numerically. To test this theory more rigorously, we analyse the whole genomes of 127 adult heartworm specimens collected from mammalian carnivore hosts across Australia, the USA, Central America, Europe, and Asia. Here we show distinct genetic differences between heartworms from different continents, indicating a more ancient dispersal in canid hosts than previously recognised. Using genetic diversity and admixture analyses, we find an Asian origin for Australian heartworms, aligning with the arrival of dingoes into Australia via Asia thousands of years ago; however, we cannot exclude the alternate hypothesis that heartworms were also introduced from Asia in post-colonial times. Finally, the genetic relatedness between European and Central American heartworms suggests that modern dispersal, potentially associated with human colonisation of the Americas by Europeans, occurred with domesticated dogs. This work sheds light on the population dynamics and deep evolutionary history of a globally widespread parasite of veterinary significance. (Figure presented.).